2015
DOI: 10.1016/j.biomaterials.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

DiameterJ: A validated open source nanofiber diameter measurement tool

Abstract: Despite the growing use of nanofiber scaffolds for tissue engineering applications, there is not a validated, readily available, free solution for rapid, automated analysis of nanofiber diameter from scanning electron microscope (SEM) micrographs. Thus, the goal of this study was to create a user friendly ImageJ/FIJI plugin that would analyze SEM micrographs of nanofibers to determine nanofiber diameter on a desktop computer within 60 seconds. Additional design goals included 1) compatibility with a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
361
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 440 publications
(387 citation statements)
references
References 53 publications
5
361
0
5
Order By: Relevance
“…Samples were mounted on aluminum stubs using carbon tape and were sputter coated with platinum using Leica EM ACE600. The average diameter and pore size of the fibrous scaffolds were analyzed using DiameterJ, 47 and ImageJ 48 software, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were mounted on aluminum stubs using carbon tape and were sputter coated with platinum using Leica EM ACE600. The average diameter and pore size of the fibrous scaffolds were analyzed using DiameterJ, 47 and ImageJ 48 software, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Small gauge (48 and 50 gauge) steel wire was chosen as an ideal material for training because 1) it has a highly uniform diameter and 2) because the diameter is large enough that it can be verified by other measurements [23]. Specific sizes of wire were chosen because they were commercially available and because they were small enough to be imaged using the “high magnification” settings within the SEM yet large enough to be sized by alternative means (calipers, light microscopy, impedance).…”
Section: Methodsmentioning
confidence: 99%
“…From SEM micrographs the most prevalent measurement made to assess nanofiber morphology is the fiber diameter. [23] Currently, manual measurement of fiber diameter from fiber SEM images is done using line tools in image analysis programs such as ImageJ/FIJI [24,25]. Recently, a publication comparing software tools and manual measurements on images of nanofibers showed that hundreds to thousands of nanofiber measures were required to converge on a consistent result.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Kurtosis for angle of orientation graphs was measured in Excel. Kurtosis is a 6 measure of "tailedness" of the probability distribution of a real-valued random variable.…”
Section: Scaffold Characterizationmentioning
confidence: 99%